Social Structures, Local Economic Development And Environmental Quality In Deprived Communities: The Case Of The Kpirikpiri Community In South-east Nigeria - Giddings, Bob; Anyigor, Kelechi; Matthews, Lesley (Penerbit Universiti Sains Malaysia, 2013)
As recently as late 2010, Africa sought a 20% increase in funding for its poor countries despite years of international aid. In 2002, Nigeria's Ebonyi State became part of the Community-Based Urban Development Project and, in 2005, joined the CommunityBased Poverty Reduction Project, both funded by the World Bank. Ebonyi focused all of the aid it received on three communities in its capital, Abakiliki. The three communities were chosen because they exhibited the lowest social, political and economic status and the highest levels of physical decay based on a survey in 2001. One of the three communities, Kpirikpiri, was surveyed again in 2010 as part of this research and in 2011, a sample of its residents participated in focus groups to evaluate how their lives had improved as a result of this funding. It was shocking to discover that the community still suffered from all five housing deprivations used by UN-Habitat to define slum conditions. Yet, the potential of these residents is high. The challenge is how to unlock their potential and establish community organisations that can apply for their own funding; develop a local economy through activities, such as home-based enterprises; negotiate with landlords, and start to improve their environmental conditions.